Respuesta :
To solve with an equation, let's call the three consecutive integers g, g+1, and g+2.
So, (g)+(g+1)+(g+2)=(g+2)+31
3g + 3 = g + 33
2g = 30
g = 15
The integers are 15, 16, and 17.
To check:
The sum of 15, 16, and 17 is 48. 17 + 31 is also 48.
Let's express this in algebraic terms:
[tex](x-2)+(x-1)+x=x+31\\x-2+x-1+x=x+31\\3x-3=x+31\\3x=x+31+3\\3x=x+34\\3x-x=34\\2x=34\\x=34/2\\x=17[/tex]
The expressions for the integers and respective values are expressed below:
[tex]x=17\\\\Integer 1 => x =17\\Integer 2 => x-1=17-1=16\\Integer 3 => x-2=17-2=15[/tex]
Now, to check, we apply the original problem and the values we discovered:
[tex](x-2)+(x-1)+x=x+31\\((17)-2)+((17)-1)+(17)=(17)+31\\(15)+(16)+17=48\\48=48[/tex]
We are right, so:
[tex]x=17\\\\Integer 1 => 17\\Integer 2 => 16\\Integer 3 => 15[/tex]